2011
DOI: 10.1002/pssa.201184253
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray diffraction characterization of microdefects in silicon crystals after high‐energy electron irradiation

Abstract: The quantitative characterization of complex microdefect structures in silicon crystals grown by Czochralski method and irradiated with various doses of high-energy electrons (18 MeV) has been performed by methods of the highresolution X-ray diffraction. The concentrations and average sizes of dislocation loops and oxygen precipitates have been determined by using the combined treatment of reciprocal space maps and rocking curves based on the analytical formulas of the statistical dynamical theory of X-ray dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The dynamic diffraction methods used in the studies of complex multilayer crystalline systems showed that these methods allow to determine the profiles of inhomogeneous in‐depth distribution of defects, and thus distinguish the near‐surface layer with a low defect concentration from the deep layer with a high defect concentration. At the same time, the sensitivity of dynamical diffraction methods allows detection of defects with a density of down to ≈10 10 cm −2 , which corresponds to ≈0.0001% of defects in a graphene lattice.…”
Section: Characteristics Of Defects: Results Of Diffraction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic diffraction methods used in the studies of complex multilayer crystalline systems showed that these methods allow to determine the profiles of inhomogeneous in‐depth distribution of defects, and thus distinguish the near‐surface layer with a low defect concentration from the deep layer with a high defect concentration. At the same time, the sensitivity of dynamical diffraction methods allows detection of defects with a density of down to ≈10 10 cm −2 , which corresponds to ≈0.0001% of defects in a graphene lattice.…”
Section: Characteristics Of Defects: Results Of Diffraction Methodsmentioning
confidence: 99%
“…Above‐mentioned concepts have been already applied to carry out a nondestructive diagnostic of the structural heterogeneities for multilayer single‐crystal heterosystems: epitaxial films of yttrium iron garnet on the substrate of gadolinium gallium garnet, which are widely used in nanoindustry. However, when structures are significantly thin, especially several layers in thick as a multilayer graphene or even single layer, the use of traditional diffraction patterns is not feasible.…”
Section: Introductionmentioning
confidence: 99%
“…After irradiation by dose of 4 × 10 15 el/cm 2 the following activation energies of RD are calculated 0.395 eV; 0.53 eV in n-Si and 0.56 eV; 0.66 eV in p-Si which stimulate conductivity because the carriers' mobility has a weak dose dependence. Among many known energetic levels in Si [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] corresponding to different RD, Figures 2-4 present energetic levels, which are identified to defined levels in literature. For example, the observed level of 0.395 eV can be classified as E-center with location on Ec 0.4 eV in the forbidden gap of Si [7][8][9]12,13], i.e.…”
Section: Resultsmentioning
confidence: 99%
“…There are numerous investigations concerning the influence of irradiations on the properties of solid states (including silicon) which are carried out before and after irradiation [for example [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The works on studying the properties of solid states directly under the irradiation process are very scarce [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…2) for the symmetrical Si(333) reflection of characteristic CuK 1 -radiation [47,48]. Additionally, the rocking curves for Si(333) reflection were measured in the -scanning mode by using the TCD with removed analyser crystal.…”
Section: Defect Structure Of the Cz-si Crystal After High-energy Elecmentioning
confidence: 99%